Public vs. Private: Who Innovates Better? A Conceptual Review of Managerial Innovation and Human Capital - Sara DIOP; Fatima OUAHRAOUI (African Scientific Journal, 2025)
Abstract This research examines the relationship between managerial innovation and human capital, focusing on the specificities of public and private contexts. Our primary objective is to decipher the impact of human capital on the managerial innovation process within these two distinct spheres. To this end, we adopt a methodology based on a systematic literature review to provide a comprehensive overview of existing knowledge. The study's findings suggest that managerial skills, organizational culture, training and development, collaboration, motivation, and adaptability are crucial dimensions of human capital influencing managerial innovation. These factors may exhibit significant variations between the public and private sectors, emphasizing the need to consider the specificities of each context. The conclusions underscore the necessity of adapting managerial approaches according to the unique characteristics of each sphere. Organizations, whether public or private, should acknowledge the central role of human capital in the managerial innovation process and develop tailored strategies to foster creativity, collaboration, and flexibility within their teams. Keywords : Managerial Innovation, Human Capital, Public Sector, Private Sector, Performance.